2017
DOI: 10.1084/jem.20160719
|View full text |Cite
|
Sign up to set email alerts
|

Rb family proteins enforce the homeostasis of quiescent hematopoietic stem cells by repressing Socs3 expression

Abstract: The mechanisms regulating the homeostasis of HSCs remain poorly understood. Here, Kim et al. identify the Rb/E2f module as a central molecular hub in the regulation of cell cycle and homeostasis in HSCs. This mechanism drives the enforced differentiation of proliferative HSCs to avoid their unnecessary accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…These include stem cell-intrinsic signaling pathways and epigenetic regulators as well as components of the micromilieu and the blood-circulatory environment [7][8][9]. Overarching principles of quiescence maintenance have been identified involving the expression of cell cycle inhibitors like p21 and p57 [10][11][12] as well as tumor suppressor genes like RB and p53 [13][14][15][16] in stem cells of different organs/tissues ( Figure 1).…”
Section: Regulation Of Quiescencementioning
confidence: 99%
“…These include stem cell-intrinsic signaling pathways and epigenetic regulators as well as components of the micromilieu and the blood-circulatory environment [7][8][9]. Overarching principles of quiescence maintenance have been identified involving the expression of cell cycle inhibitors like p21 and p57 [10][11][12] as well as tumor suppressor genes like RB and p53 [13][14][15][16] in stem cells of different organs/tissues ( Figure 1).…”
Section: Regulation Of Quiescencementioning
confidence: 99%
“…35,37 We also found that Jmjd6 deficiency results in upregulation of other pathways whose activity is known to deplete or exhaust HSCs, including mTORC1 signaling, 39 protein synthesis, 40 and E2F downstream pathway. 41 Notably, although our findings reveal JMJD6 as a suppressor of multiple pathways, whose excessive activation promotes HSC failure, the mechanisms through which JMJD6 functions in this context remain an open question, meriting further investigations. Finally, we revealed that JMJD6 is unlikely to be a major splicing regulator in HSCs.…”
Section: Discussionmentioning
confidence: 80%
“…To mechanistically understand the failure of Jmjd6-deficient HSCs upon serial transplantation, we examined the molecular signature of Jmjd6-deficient LSK cells. Although differential gene expression analysis identified a number of individual deregulated genes (supplemental Figure 4), GSEA indicated a broader upregulation of processes detrimental to HSCs, including p53 activity 35,37 (which is known to be directly repressed by JMJD6 7,17 ), G 1 /S and G 2 /M checkpoints, OXPHOS, 38 mTORC1 signaling, 39 protein synthesis, 40 and E2F signaling 41 (Figure 4A-B). Given that suppression of OXPHOS is essential for HSC self-renewal, and its upregulation devastates HSC functions, 38 we validated the impact of Jmjd6 deletion on OXPHOS using a Seahorse XF Analyzer.…”
Section: Jmjd6 Suppresses Oxphos and Ros Generation To Control Hematopoiesismentioning
confidence: 99%
“…Gene set enrichment analysis (GSEA) indicated a broad dysregulation of multiple pathways and processes, which was compatible with the loss of HSC function. Notably, we found that Cited2-deficient HSCs displayed activation of proinflammatory pathways, c-MYC and E2F targets, and K-RAS and mTORC1 signaling, whose elevated activity is known to lead to HSC exhaustion or loss of their reconstitution potential (Kim et al, 2017;Pietras, 2017;Sasine et al, 2018;Wilson et al, 2004;Yilmaz et al, 2006) (Figures 5B and 5C). Consistent with upregulation of E2F and c-MYC targets, analysis of proximal promoters of upregulated genes revealed the presence of E2F and c-MYC motifs, suggesting that CITED2 may repress E2Fs and c-MYC (Figure 5D).…”
Section: Cited2 Maintains Hscs By Regulating Mcl1 Expressionmentioning
confidence: 99%